Survival differences between women and men in the non-reproductive cancers: Results from a matched analysis of the surveillance, epidemiology, and end-results program - Luz, Felipe Andrés Cordero da; Nascimento, Camila Piqui; Marinho, Eduarda da Costa; Felicidade, Pollyana Júnia; Antonioli, Rafael Mathias; Araújo, Rogério Agenor de; Silva, Marcelo José Barbosa (Frontiers in Public Health, 2023)
Background Men with non-reproductive cancers have a discrepant outcome compared to women. However, they differ significantly in the incidence of cancer type and characteristics. Methods Patients with single primary cancer who were 18 years or older and whose data were gathered and made accessible by the Surveillance, Epidemiology, and End Results (SEER) program were included in this retrospective analysis. Kaplan-Meier curves and Cox regression before and after propensity score matching were performed to analyze the risk survival by sex. Results Among the 1,274,118 patients included [median (range) age, 65 year (18–85+) years; 688,481 (54.9%) male]. The median follow-up was 21 months (0–191). Substantial improvements in survival were observed for both sexes during the years of inclusion analyzed, with no difference between them, reaching a reduction of almost 17% of deaths in 2010, and of almost 28% in 2015, compared to 2004. The women had a median survival of 74 months and overall mortality of 48.7%. Males had a median survival of 30 months (29.67–30.33) with an overall mortality of 56.2%. The PSM showed a reduced difference (6 months shorter median survival and 2.3% more death in men), but no change in hazards was observed compared to the unmatched analysis [adjusted HR: 0.888 (0.864–0.912) vs. 0.876 (0.866–0.886) in unmatched]. Conclusions The discrepancy in survival between men and women is not explained only by the incidence of more aggressive and more advanced cancers in the former.